MASLD treatment—a shift in the paradigm is imminent - Machado, Mariana Verdelho (Frontiers in Medicine, 2023)
MASLD prevalence is growing towards the leading cause of end-stage liver disease. Up to today, the most effective treatment is weight loss. Weight loss interventions are moving from lifestyle changes to bariatric surgery or endoscopy, and, more recently, to a new wave of anti-obesity drugs that can compete with bariatric surgery. Liver-targeted therapy is a necessity for those patients who already present liver fibrosis. The field is moving fast, and in the near future, we will testify to a disruptive change in MASLD treatment, similar to the paradigm-shift that occurred for hepatitis C almost one decade ago with direct antiviral agents.